EVALUASI KUALITAS FISIK SILASE BERBASIS DEDAK YANG DISUBTITUSI DENGAN AMPAS TAHU - Moch Ikhsanudin; Lestariningsih; Binti Khopsoh (Wahana Peternakan, 2026)
Silage is a feed obtained through a fermentation process that can help overcome the problem of feed shortages for livestock. The use of local materials such as rice bran and tofu dregs make silage has the potential to increase nutritional content and reduce the amount waste. The purpose of this study was to assess the physical quality of silage by observing odor, color, texture, mold, and pH. This research was carried out experimentally with a Completely Randomized Design (CDR) design, including five treatments and four replications. To analyze the data, ANOVA was used to determine the effect of tofu pulp substitution on silage quality. The results showed that the P2 treatment (525 grams of tebon, 225 grams of brain, and 250 grams of tofu dregs) produced silage with a slightly brown color, typcal fermentation odor, dense and moist texture, pH 4.15 and without mold. After being analyzed, the substitutions of tofu pulp greatly affects the physical quality of silage, except for the presence of fungi which is not significantly different. The conclusion of this study is that the use of tofu pulp up to 250 grams in the silage formulation (P2) improves the physical quality, but the addition of more decreases the quality of silage. This research is expected to support the utilization of local ingredients as an efficient and sustainable alternative feed.